Предмет: Математика,
автор: dasavyborna558
-(ab+4ac-3bc)-3(2ab-ac-bc)
при a=1,2; b=-2,4; c=-1,8
допоможіть!!
Ответы
Автор ответа:
1
Ответ:
101,376
Пошаговое объяснение:
-(ab+4ac-3bc)-3(2ab-ac-bc)
при a=1,2; b=-2,4; c=-1,8
-ab-4ac+3bc-6ab+3ac+3bc=-1,2*(-2,4)-4*1,2*(-1,8)+3*(-2,4)*(-1,8)-6*1,2*(-2,4)+3*1,2*(-1,8)+3*(-2,4)*(-1,8)=101,376
Похожие вопросы
Предмет: Английский язык,
автор: meowken
Предмет: Окружающий мир,
автор: Anyashcolnik2016
Предмет: Английский язык,
автор: Maria6754587
Предмет: Алгебра,
автор: Гуля551
Предмет: Математика,
автор: VorogSHOw